Non-fullerene acceptor based photoelectric material for retinal prosthesis - Hyunsun Song; Roh, Hyeonhee; Kim Jae Young; Lee, Byung Chul; Walker Bright; Im, Maesoon (Springer, 2023)
Microelectronic retinal implants can restore a useful level of artificial vision in photoreceptor-damaged retina. Previously commercialized retinal prostheses require transocular connection lines to an external power supply and/or for data transmission, which are unwieldy and may cause unwanted side effects, such as infections. A recently reported wireless device used a rigid silicon substrate. However, it had the potential for a long-term mechanical mismatch with soft retinal tissue. In this work, we used organic photovoltaic materials which can be fabricated on flexible substrates as well as be operated without any physical connection to the external world. The present study employed PCE10 as an active layer for retinal prosthetic application for the first time. Compared to previously studied organic photovoltaic materials used in retinal prosthesis research (such as P3HT), our PCE10 devices showed higher efficiency, providing a huge advantage in this field. When the PCE10 was blended with other non-fullerene acceptors achieving a ternary organic photovoltaic layer (PCE10:ITIC:Y6 blend), it showed lower reduction of photocurrent under same irradiation frequency condition. The fabrication method for our organic photovoltaic device was simple and easy to control its thickness. The fabricated devices showed adequate photocurrent to stimulate the retinal neurons with a smaller reduction in generated photocurrent during repeating stimuli compared to P3HT or PCE10 alone.Author names: Please confirm if the author names are presented accurately and in the correct sequence (given name, middle name/initial, family name). Author: Given name [Jae Young] Last name [Kim]. Author: Given name [Byung Chul] Last name [Lee].Yes, they are correct.